Fighting to be God: A Bourdieusian critique of the challenge of humanitarian disarmament to the State - Vargas, Ivar (2026)
This article examines the epistemic and critical potential of the Bourdieusian notion of the State as a dual monopoly of legitimised physical and symbolic violence. Despite growing use of Bourdieu’s sociological theory in International Relations over the past two decades, this notion remains underexplored in a highly relevant area: the analysis of humanitarian disarmament. It is precisely this notion, I argue, that enables a more precise, nuanced understanding about how humanitarian disarmers challenge not the State’s monopoly over lethal force, but its exclusive control over determining il/legitimate means of violence. By scrutinising the discourse of the Campaign to Stop Killer Robots, the article demonstrates how campaigners compete with the State’s claim to act for the universal interest with their own invocations to the universalist discourse of humanity. Their universal affectations, however, are confined to the sanctity of the liberal State as the authorised holder of the right to wage war.